Frank R. Pote, Harry Ober, John M. McNaught, Arthur Milhench, and Francis P. Hazel, Class of 1941 Liberal Arts students, ca. 1937-38 - Munro, Melville S. (Tufts Archival Research Center, 2005)
Print is in Munro Collection, Box 071, p. 27, #13119